Antibiotypes and high frequency of toxin genes in methicillin-resistant Staphylococcus pseudintermedius from nares of dogs and dog guardians in Nigeria. (October 2022) - Moses, Ikechukwu Benjamin; Esimone, Charles Okechukwu; Iroha, Ifeanyichukwu Romanus; Rubin, J.E.; Sniatynsky, M.K.; Ribeiro, Ághata Cardoso da Silva; Santos, Fernanda Fernandes; Cayo da Silva, Rodrigo; Gales, Ana Cristina
Abstract: To determine the antibiotypes and frequency of toxin genes in methicillin-resistant Staphylococcus pseudintermedius (MRSP), 281 nasal swab samples were collected from dogs and dog guardians in Abakaliki, Southeastern Nigeria. Antimicrobial susceptibility testing was determined by disc diffusion technique while detection of toxin genes was carried out by PCR. Exactly 41 (28.7 %) and 6 (4.3 %) MRSP were obtained from dogs and dog guardians respectively. Isolates exhibited resistance (100–16.7 %) to amoxicillin-clavulanic acid, cephalosporins, fluoroquinolones, and carbapenems. Sec canine, lukD, siet, and exi toxin genes were harboured by 42 (89.4 %), 47 (100 %), 37 (78.7 %), and 2 (4.3 %) MRSP isolates respectively. This study has shown that dogs and dog guardians in Abakaliki, Southeastern Nigeria are colonized by multiple drug-resistant MRSP which harbour toxin genes. This represents a significant public health problem in veterinary and human medicine. Highlights: This study showed that dogs and dog guardians in Nigeria are colonized by methicillin-resistant S. pseudintermedius (MRSP). MRSP isolates in this study were multiple-drug resistant and harbour Sec canine, luk D, siet, and exi toxin genes. Sec canine, luk D, and siet toxin genes in MRSP might possibly play an important role in the pathogenesis of infection. Exi toxin genes are not very common among MRSP isolated from dogs and dog guardians in Southeastern Nigeria. This study will be of great significance to the One Health programme in tackling zoonotic and anthropozoonotic diseases.